Planes de vida como estrategia para la transformación y fortalecimiento de la comunidad de San Antonio del Río Pintuyacu - Loreto, periodo 2024 - Ihuaraqui Tafur, Christina Myshel (2025)
The present study, with a quantitative approach and non-experimental, descriptive correlational and transversal design, was carried out in the community of San Antonio, Pintuyacu River in the Nanay River basin, where life plans were implemented. The sample was made up of all the families that participated in said implementation, reaching a total of 57 families, through census sampling. For data collection, a survey was used whose reliability was determined using Cronbach's Alpha coefficient (0.881) in an 18-item instrument. The normality of the data was evaluated using the Kolmogorov-Smirnov test, which justified the use of the Spearman correlation coefficient for statistical analysis. The results showed that life plans constitute a fundamental tool to strengthen social cohesion in the native communities of the Pintuyacu River, promoting greater participation and internal communication that favors collective work and community self-management. Likewise, it was determined that these instruments have promoted processes of socio-productive transformation, facilitating the identification and development of economic opportunities based on traditional knowledge and strategies adapted to the resources of the territory. However, the implementation of life plans has revealed deficiencies in critical aspects such as technical training, inter-institutional coordination and access to financing, which limits their effectiveness and sustainability over time. In this sense, the need to establish systematic monitoring and evaluation mechanisms that allow continuous feedback, optimization of planning strategies and dynamic adaptation to sociopolitical and environmental changes in the community is highlighted.